Inducibility of atrial fibrillation after catheter ablation predicts recurrences of atrial fibrillation: a meta‐analysis. Issue 4 (17th March 2021) - Millenaar, Dominic; Becker, Nicolas; Pavlicek, Valérie; Wintrich, Jan; Böhm, Michael; Mahfoud, Felix; Ukena, Christian
Abstract: Background: Pulmonary vein isolation (PVI) is a component of standard care for patients with symptomatic atrial fibrillation (AF). Procedural inducibility of AF following PVI has been suggested as predictor of AF recurrence but is discussed controversially. This meta‐analysis aimed at evaluating the relevance of electrophysiological inducibility of AF following PVI for future AF recurrences. Methods: A literature search of MEDLINE and Web of Science was performed until April 2020. Prospective trials of PVI in patients with AF and post‐procedural atrial stimulation to test for inducibility of AF as well as adequate follow‐up for AF recurrence (defined as AF >10 s to >10 min at follow‐up) were included. Odds ratios (ORs) were analyzed using random‐effects models. Results: A total of 11 trials with 1544 patients (follow‐up 7–39 months, age 56 ± 6 years, predominantly male 74 ± 6%) were included. Inducibility of AF post‐PVI was predictive for AF recurrence during follow‐up (OR 2.08; 95% CI 1.25 to 3.46). Prediction for AF recurrence at follow‐up was better for patients with paroxysmal AF (OR 4.06; 95% CI 1.39 to 11.91), stimulation in the CS (OR 2.82, 95% CI 1.17 to 6.79). A trend towards higher ORs was seen without the use of isoproterenol (OR 2.43; 95% CI 1.17 to 5.07), as well as few stimulations during induction and a short definition of AF in meta‐regression analyses. Conclusions: Electrophysiological inducibility of AF following PVI was predictive for future recurrence of AF, in particular in patients with paroxysmal AF, stimulation in only CS and no use of isoproterenol.